Modeling and control of compact anthropomorphic robot finger - Zainul Azlan, Norsinnira; Yamaura, Hiroshi (2011)
This paper presents the development of the mathematical model and controller of a light weight and small size robot finger. The finger possesses self adaptive grasping capability and is made of seven bar linkages with a slider or lead screw mechanism in the middle phalanx to adjust its effective length in realizing both pinching and grasping tasks. The dynamic model of the linkages is integrated with the electrical motors mathematical description to represent the whole robotic system. Numerical simulations have been carried out to study the finger’s dynamic behaviour under the Proportional Integral Derivative (PID) control.